Failure Mode Assessment in Production Line by Using FMEA and RPN Method: Enhancing Risk Management in Production Line using Improved FMEA and RPN Method (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The risk management program comprises of four main components risk control, risk assessment, risk communication, as well as risk review. Each four component is crucial. All the above methods should address on the mentioned four basic components. Team selections as well as technique selection have also been playing an important role in the risk management process, so attention should be given while assortment of risk management team as well as approaches. FMEA has been a better approach for risk management in the pharmaceutical industry by means of FMEA analysis comprise greater reliability, better quality, enhanced safety as well as its contribution for cost saving comprises reduced development time as well as lessened waste and non value added processes. Conventional FMEA has some shortcomings, and in this work, it has been improved by improving the RPN number and optimizing results of production line.